Sistem Pembagian Waris Menurut Adat Bugis dalam Perspektif Hukum Islam di Kecamatan Banyuasin II Kabupaten Banyuasin - Abdul Jafar; Dea Justicia Ardha (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The implementation of the division of inheritance according to bugis customary law in Banyuasin II district, Banyuasin regency. The Bugis people are adherents of the inheritance system drawing the lineage of the Father (Patrilinial). The implementation of the division of heirs in the Bugis community is carried out first by the deliberation of the heirs, in the form of family deliberations carried out by the heirs. The deliberation of the consensus occurred due to the presence of an aged heir (the eldest son) or the existence of family harmony among the heirs. Judging from the perspective of Islamic inheritance law, there are many similarities, but nevertheless it is inseparable from the differences between these two inheritance law systems. The problem in this study is to study and examine the division of inheritance according to Bugis customs in the Perspective of Islamic law? This study uses normative research by using secondary data as the main data and supported by primary data as additional data and does not intend to test hypotheses. The process of dividing bugis customary inheritance in Banyuasin Regency, does not know how to calculate mathematics, as Islamic inheritance law distributes certain parts to the heirs according to their respective positions but is always based on consideration of the results of deliberations, appropriateness, harmony considering the form of objects and the provisions of the applicable inheritance law. The division of inheritance in bugis society of boys gets more shares than the amount obtained by girls.